2021
DOI: 10.3390/en14216867
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Review of Sustainable Product Design

Abstract: Consideration of sustainability in product development is becoming increasingly important and encompasses many aspects of product design. In this study, a bibliometric review of recent sustainable product design publications using Web of Science and VOSViewer is carried out. The review indicates that the majority of publications concerning sustainable product design is oriented towards environmental science-led subject areas and production-led journals. Analysis of author keyword co-occurrences reveals that ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Studies that use bibliometrics in reviewing the literature on the design methods for the elderly remain scarce and are mainly conducted from a sustainability perspective. For example, Jiang et al [36] conducted a bibliometric review of the recent publications on sustainable product designs and the keywords used in the Web of Science database. Geng et al [37] proposed the concept of user-oriented sustainable design by using keywords related to sustainable design and user-centered design to obtain articles from the Scopus database.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies that use bibliometrics in reviewing the literature on the design methods for the elderly remain scarce and are mainly conducted from a sustainability perspective. For example, Jiang et al [36] conducted a bibliometric review of the recent publications on sustainable product designs and the keywords used in the Web of Science database. Geng et al [37] proposed the concept of user-oriented sustainable design by using keywords related to sustainable design and user-centered design to obtain articles from the Scopus database.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainability issues of a product need to be addressed as early as possible in the design process, whereas most of the sustainability support tools can only be employed at late design stages (Jiang et al, 2021). For example, life cycle assessment, which is the most often used tool for supporting sustainable product design (Deng et al, 2016), measures the environmental impacts of a product along its life cycle (Rossi et al 2016).…”
Section: Sustainable Product Designmentioning
confidence: 99%
“…Many attempts have been made to quantify the process but all suffer from the same issue that there are too many options which often makes the process null and void. Besides, in a recent study, Jiang et al (2021) revealed that current research failed to establish associations between product design activities and sustainability through a bibliometric review of over 7000 academic publications concerning sustainable product design. The study indicated that the lack of design research for supporting sustainable product design has led to challenges in producing products that are more sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…However, CLDs can also be the basis for agent-based models (Abbot & Hadžikadić, 2017). In a sustainable product development context, GMB is therefore useful prior to deployment of other systems-or relationship-modeling techniques, such as functional modeling, design structure matrix, and quality-function deployment, that are commonly used in product development, e.g., (Ayağ, 2021;Jiang et al, 2021;Watz & Hallstedt, 2018b).…”
Section: Introductionmentioning
confidence: 99%